Strategi Guru (SAGU) dalam implementasi HOTS pada Pembelajaran di SD INPRES Polder Merauke: Sebuah Analisis - Nirtha, Eva; Rival Hanip; Yonarlianto Tembang (Universitas Kristen Satya Wacana, 2024)
High Order Thinking Skills (HOTS) are crucial in the education era of Revolution 5.0, requiring teachers to incorporate these skills into their teaching. However, many teachers face challenges in fully implementing HOTS due to various internal and external factors. This qualitative descriptive study analyzes the strategies used by teachers at SD Inpres Polder in Merauke for implementing HOTS. The research involved 18 teachers and employed data collection techniques such as in-depth interviews, classroom observations, and documentation studies of lesson plans and curricula. The results indicate that teachers employ several strategies to integrate HOTS, including designing learning activities and tasks oriented towards HOTS, providing feedback to develop thinking skills, and collaborating with students for complex problem-solving. Additionally, they use resources that stimulate reflective and critical thinking. However, teachers also encounter challenges such as limited time, curriculum adjustments, and diverse student backgrounds. In conclusion, while teachers at SD Inpres Polder have adopted various strategies to implement HOTS, they need further support to enhance these strategies. Collaborative efforts from schools, parents, and policymakers are essential to help teachers develop their professionalism and effectively apply HOTS in their teaching.